Elucidating structural basis of benzofuran pyrrolidine pyrazole derivatives for enhancing potency against both the InhA enzyme and intact M. tuberculosis cells: a combined MD simulations and 3D-QSAR study1. Issue 65 (16th July 2015) - Kamsri, Pharit; Punkvang, Auradee; Hannongbua, Supa; Saparpakorn, Patchreenart; Pungpo, Pornpan
<x xml:space="preserve">Abstract</x> The structural concept for enhancing both IC50 and MIC90 activities summarized from MD simulations and CoMSIA results.